That boy who swears by his wit, wisdom, and willpower / Mia Emily Abdul Rahim - Abdul Rahim, Mia Emily (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.